PENGARUH UKURAN PERUSAHAAN, LIKUIDITAS DAN RESIKO BISNIS TERHADAP STRUKTUR MODAL PADA PERUSAHAAN PERTAMBANGAN YANG LISTING DI BURSA EFEK INDONESIA - Mirawati Sofiani Putri; Nurul Huda (Jurnal Revenue : Jurnal Ilmiah Akuntansi, 2022)
This study aims to determine the effect of firm size, liquidity and business risk on capital structure. The method used is a quantitative research approach. The reults of the study show that (1) Firm size and liquidity partially have no significant effect on capital structure. (2) Business risk partially has a significant effect on capital structure. (3) Company size, liquidity and business risk simultaneously have a significant effect on capital structure